Design and Construction of the Triple-Layer Counter Flow Concentric Tube - Manik, Terang UHSG.; Rinkanto, M.; Zulkifli, A. (TALENTA Publisher, 2022)
A heat exchanger is a device that produces the transfer of heat from one fluid to another. The study aims to design and build a concentric three-prototype with counterflow to lower the temperature of the hot fluid. The hot fluid flows in the annular part of the second copper tube, and then the cold fluid flows into the third copper tube each through the first copper tube and the annulus. The hot fluid is water at 60ÂºC, a 1000-watt water heater is used to heat the fluid, and the cold fluid is air at 25ÂºC. The total length of the four concentric prototypes is the first 2.57-meter diameter copper tube. The diameter of the second copper pipe is 2.22 m1 inch. The copper pipe is 1.74 m long and 13/4 inches in diameter. The fluid that can be measured by a fluid thermometer in and out of the heat exchanger is the thermocouple, which is then processed by the computer through the installation of data acquisition modules and tracerdag software.